An investigation into the implementation of green building features and initiatives among stakeholders in the Zambian property market - Katanekwa, Luse Namutowe (Department of Construction Economics and Management, 2020)
There is a global challenge and demand in the current century to develop buildings that conserve and preserve the environment; implementing green building features and initiatives (GBFIs) is one way to achieve this. The success of implementing GBFIs requires inclusive participation of the stakeholders in the property market. A multiple case study analysis was conducted on the Zambian Property market, involving three buildings that had different GBFIs. A total of six interviews were conducted across the three cases with relevant stakeholders, namely Facilities managers, tenants, project architect and regulatory body representative. Interviewees were asked questions pertaining to their company’s participation in the development of green building, the benefits of GBFIs, the perception of GBFIs, the relationships among stakeholders as well as the impact of GBFIs in the property market. The findings revealed that there were different approaches to implementing GBFIs. However, a lack of knowledge by some stakeholders on green features and their benefits was noted. This lack of knowledge was a product of inadequate education and poor integration of stakeholders in implementing GBFIs in the Zambian property market. It is important to note that there are vigorous efforts by stakeholders including the government in contributing to conserving the environment in the Zambian property industry. This is evident in the formulation of green building guidelines and environmental impact assessment guidelines for the construction industry.